Pengolahan Batubara dan Pemanfaatannya untuk Energi - Edy Nursanto (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2015)
The processing of coal has conducted to removing impurities in coal. Stages remove impurities in coal that is preparation, concentration and dewatering. Preparation is reduction size of coal, concentration to remove of impurities, while dewatering to reduce of water content in coal after concentration process. Result ofcoal processing will use to energy as well as direct andconversion fuel. The development of Indonesian coal industry on lastyears have increased be in accordance with growth  of economic. In the future coal is utilization as an energy source that it will increase especially as a direct and conversion fuel. Direct coal fuel can use to power  generation, cement factory, home industry and domestic. In the other hand coal conversion fuel is convertedinto oil or liquefied coal, gas and carbonization.